A descriptive analysis on operation strategy and procedure of special asset management department of IDLC Finance Limited - Sanjida, Nafisa (BRAC University, 2017)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2016.